Microinvasive Glaucoma Surgery: An Evidence-Based Assessment - Schehlein, Emily M. (Expert Rev Ophthalmol, 2017)
INTRODUCTION: The advent of Microinvasive Glaucoma Surgery (MIGS) offers a novel approach in the treatment of glaucoma with the number of procedures developing at an exciting pace. AREAS COVERED: MIGS procedures aim to lower intraocular pressure (IOP) via four mechanisms: (1) increasing trabecular outflow, (2) increasing outflow via suprachoroidal shunts, (3) reducing aqueous production, and (4) subconjunctival filtration. A comprehensive search for published studies for each Microinvasive Glaucoma Surgery (MIGS) device or procedure was undertaken using the electronic database PubMed. Search terms included ‘minimally invasive glaucoma surgery’, ‘microincisional glaucoma surgery’, and ‘microinvasive glaucoma surgery’. A manual search for each device or procedure was also performed. After review, randomized control trials and prospective studies were preferentially included. EXPERT OPINION: These procedures offer several benefits: an improved safety profile allowing for intervention in earlier stages of glaucoma, combination with cataract surgery, and decreased dependence on patient compliance with topical agents. Established MIGS procedures have proven efficacy and more recent devices and procedures show promising results. Despite this, further study is needed to assess the long term IOP-lowering effectiveness of these procedures. Particularly, rigorous study with more randomized control trials and head-to-head comparisons would allow for better informed clinical and surgical decision-making. MIGS offers new solutions for glaucoma treatment.